Improving weekend handover between junior doctors on medical and surgical wards. Issue 2 (3rd January 2014) - Bethune, Rob; Campbell, Kate; Rose, Alex; Wassall, Richard; Price, Catherine; Siese, Thomas; Finn, Roisin; Whitaker, Sean
Abstract: Poor weekend handover has been implicated as one of the causes of observed higher mortality rates at weekends in UK hospitals. In a large teaching hospital we, a group of junior doctors, set about improving the quality and effectiveness of weekend handover. We used the Model for Improvement to implement a weekend handover sticker through an iterative process using multiple Plan/Do/Study/Act (PDSA) cycles. Over the 16 week study period the number of completed weekend tasks increased by 30% and the number of patients with a documented weekend handover increased by nearly 50%. Junior doctors are well positioned to notice the quality and safety shortcomings within hospitals, and by using effective improvement methods they can improve these systems at little or no cost.